Development of dc-dc converter for dc motor using fuzzy logic controller - Yusof, Mohd Faiz Husny (2013)
When the DC motor is turned on, the start dc motor speed will experience overshoot at the starting speed of the motor. This overshoot will affect the current rise high as if connected to a load. The use of conventional controllers has long been used to control the dc motor and reduce overshoot starting. Fuzzy logic controller is one controller that can be used to control the speed of a dc motor including motor control overshoot starting. To see the effectiveness of fuzzy logic controller in dc motor speed control, a study done by designing a conventional two-Integrated controllers of proportional controller (PI) and proportional-Integrated-Derivatives controller (PID) and compared with fuzzy logic controller. The design of Fuzzy Logic Controller (FLC) does not require an exact mathematical model. Instead, it is design based on general knowledge of the plant. Both three controllers are connected to a dc motor as a load to control the motor speed to the required level. The effectiveness of the designed FLC is compared with designed conventional controllers to examine aspects of starting overshoot, settling time and ripple factor for dc motor speed.